Peran Guru di Sekolah dalam Mengurangi Tingkat Stres Akademik Peserta Didik SMP - Muhammad Almaida Alfarizi; Desy Safitri; Sujarwo (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
This research was motivated by the academic stress level of junior high school (SMP) students aged 14-19 years who experienced moderate to high levels of stress. The increase in academic stress in students in this age group is due to stressors during adolescence, the transition period from childhood to adulthood. The era of globalization in Indonesia is shifting the educational paradigm which prioritizes Human Resources over Natural Resources. The Student Centered Learning approach shifts the role of the teacher from someone who conveys knowledge to students to someone who supervises students in acquiring knowledge on the internet. However, misperceptions in its application trigger academic stress in students aged 14-19 years. Apart from formal education, stress triggers for students can also be caused by non-formal education, such as parental guidance at home. The increase in study time and increased pressure for students to understand school subjects causes an increase in academic stress levels every year, especially among children aged 14-19 years. An increase in academic stress in students aged 14-19 years was seen when the Distance Learning program was implemented during the Covid-19 pandemic that hit the whole world, including Indonesia. The increasing academic stress in children aged 14-19 years requires teachers to understand and reduce the stress levels of their students with a good approach through the application of learning methods, religious counseling assistance and other positive activities that can be useful in reducing the academic stress of children aged 14-19 years.